DINAMIKA HMI DAN KAMMI DI KOTA DENPASAR 1990--2014 (KAJIAN TENTANG POLA IDEOLOGI GERAKAN MAHASISWA ISLAM) - Armando, Ragil (Humanis; Volume 15. No.1. April 2016, 2016)
This journals discusses the background of the Islamic student movement formation in Denpasar and the contribution of Islamic student movement, especially HMI and KAMMI in national development and in Denpasar , as well as the patterns of the ideology that forms the character of HMI and KAMMI as the Islamic student movement. The theory used in this research is the theory of explanation in which describes the explanation and describes a meaning , prepared on the historical explanations procedures accordingly so that instead of being a fantasy story. In addition, also used multicultural theory, social movements theory, and political opportunity structure theory as the theory supporting. There are four methods used in this research, namely (1) heuristic methods; (2) source criticism; (3) the method of interpretation; and (4) a method of historiography.
Keywords: HMI, KAMMI, Denpasar, Gerakan, Mahasiswa Islam